The influence of calcium chloride deicing salt on phase changes and damage development in cementitious materials. (November 2015) - Farnam, Yaghoob; Dick, Sarah; Wiese, Andrew; Davis, Jeffrey; Bentz, Dale; Weiss, Jason
Abstract: The conventional CaCl2 –H2 O phase diagram is often used to describe how calcium chloride behaves when it is used on a concrete pavement undergoing freeze-thaw damage. However, the chemistry of the concrete can alter the appropriateness of using the CaCl2 –H2 O phase diagram. This study shows that the Ca(OH)2 present in a hydrated portland cement can interact with CaCl2 solution creating a behavior that is similar to that observed in isoplethal sections of a ternary phase diagram for a Ca(OH)2 –CaCl2 –H2 O system. As such, it is suggested that such isoplethal sections provide a reasonable model that can be used to describe the behavior of concrete exposed to CaCl2 solution as the temperature changes. Specifically, the Ca(OH)2 can react with CaCl2 and H2 O resulting in the formation of calcium oxychloride. The formation of the calcium oxychloride is expansive and can produce damage in concrete at temperatures above freezing. Its formation can also cause a significant decrease in fluid ingress into concrete. For solutions with CaCl2 concentrations greater than about 11.3% (by mass), it is found that calcium oxychloride forms rapidly and is stable at room temperature (23 °C).